Savings, investment, and capital mobility - Gochoco-Bautista, Maria Socorro H. (1995)
This study exploits the relationship between savings and investment implied by a country's inter temporal budget constraint to measure the degree of capital mobility. In particular, if savings and investment are cointegrated, there is an error correction model which describes the short run dynamic behavior of savings and investment. If the degree of capital mobility is greater, we would expect the dynamic responses of savings and investment to shocks to be larger. Using annual data for the Philippines from 1946-1994, the study's findings are largely consistent with the hypothesis that capital mobility increased in the post-Bretton Woods period. The only finding that is not supportive of this is that which shows the contribution of US shocks to the variance of the forecast errors of Philippine saving and investment declining in the post-Bretton Woods period.
Includes bibliographical references (page 17).
Keywords: Saving and investment; Economics -- History -- 1946-1994.